GOING BEYOND THE NUMBERS: COSTING STRATEGIES FOR SUSTAINABLE DECISIONS AND ORGANIZATIONAL SUCCESS - Luis Corrêa Magno, André (Revista Gênero e Interdisciplinaridade, 2025)
Costing strategies are essential tools for improving management, as they encompass quantitative measurement processes with distinct purposes, yet aligned with organizational scopes, balancing financial, operational, and contextual data in the face of current challenges that require the integration of ESG criteria, digital technologies, and continuous professional development. Organized cost control promotes informed decisions, aligning profitability, social responsibility, innovation, and sustainability, aiming for organizational prosperity.